Reduction of Harmful Emissions at Power Plants by Controlling Optimal Fuel Flow Rate for Boiler Burners Ignition - Stepan Mysak; Marta Martynyak-Andrushko; Anna Hyvlud; Marta Kuznetsova (Energy Engineering and Control Systems)
This research work focuses on the study of the issue of the effective use of natural gas and fuel oil for the ignition of pulverized coal torches of boilers at thermal power plants. The main goal of this work is to conduct an analysis of experimental studies and identify the optimal flow rate of natural gas and fuel oil, which ensure the most effective and economical ignition of a pulverized coal torch. Namely, the test results of TPP–210A boiler when burning coal with natural gas ignition at the flow rate of 6,000 m3/h, 10,000 m3/h, 14,000 m3/h or 12%, 21%, 30% by heat were given and analyzed. The influence of operating mode factors on the economic indicators of the boiler and the output of liquid slag has been demonstrated, and their optimal values have been determined. With the optimal values of the mode factors, the economic and ecological indicators of the boiler have the following values: gas flow rate for ignition is 6,000 m3/h – 10,000 m3/h; content of combustibles in the take away ashes is 21% – 16%; boiler efficiency is 84.52% – 86.73%; amount of NOx emission is 665 mg/m3 – 740 mg/m3. It has been experimentally proven that the minimum gas flow rate at which optimal boiler operation conditions are ensured in terms of efficiency and liquid slag output is 10,000 m3/h, under the condition of uniform distribution of gas to all burners.